KESUKAAN KONSUMEN TERHADAP BAKSO AYAM: PERBANDINGAN BERBAGAI JENIS DAGING AYAM DENGAN TEPUNG MOCAF SEBAGAI BAHAN PENGISI - Nurul Hidayati; Sri Sari Utami (Jurnal Pertanian Agros, 2025)
Chicken meatballs are a popular processed meat product enjoyed by various groups of people. This study aims to evaluate consumer preferences for chicken meatballs made with different types of chicken meat and mocaf flour as a filler. The types of chicken used in the study included free-range chickens and broiler chickens. A Complete Random Design (RAL) was utilized with five treatments: P1: 100% free-range chickens; P2: 75% free-range chickens and 25% broilers; P3: 50% free-range chickens and 50% broilers; P4: 25% free-range chickens and 75% broilers; P5: 100% broilers. Each treatment was repeated three times. The parameters observed in the study included consumer preferences for color, aroma, texture, chewiness, taste, and overall assessment of the meatballs. Data were analyzed using ANOVA, followed by the Duncan test at a 5% confidence level. The study's results indicated that the type of chicken used had no significant impact on consumer preferences regarding color, aroma, or overall assessment of the meatballs. However, it did have a significant effect on consumer preferences for texture, chewiness, and taste. These findings provide valuable insights into how the type of chicken meat influences the sensory characteristics of meatballs, as well as the potential of using mocaf flour as a filler to enhance the quality of processed chicken products.